ECONOMIC POTENTIAL OF CENTRAL SULAWESI AS SUPPLY AREAS FOR THE NEW CAPITAL CITY OF INDONESIA - Failur Rahman; Sofia Ikhromi; Meity Ferdiana Paskual; Muhammad Ichsan (International Journal of Accounting, Finance and Business, 2023)
Currently, Indonesia is carrying out a program to move the national capital from Jakarta to North Penajam Paser Regency, East Kalimantan Province. The relocation of the nation's capital will lead to an increase in population as well as an impact on increasing demand for food and non-food consumption needs. This study aims to determine the possibility of increased consumption as a result of population growth. In addition, this research is also aimed at knowing the base sector of Central Sulawesi Province which has potential as a supply area. The research show that population growth reached 179.83% with an estimated expenditure on food consumption of 6139.4% and an estimated expenditure on non-food consumption of 6011.7%. Research shows potential sub-sectors that need to be developed and can improve the regional economy, including: sub-sector of Basic Metal Industry; Metal Ore Mining sub sector; sub sector of plantation crops; forestry and logging sub sector; mining and other quarrying sub-sector; the sub-sectors of Wood Industry, Products from Wood and Cork and Woven Products from Bamboo, Rattan and the Like; fisheries sub-sector; sub-sector of agriculture and hunting services; Horticultural Plants sub sector; and sub-sector of the Oil, Gas and Geothermal Mining.